Kandungan Senyawa Bioaktif dan Aktivitas Biologis Ekstrak Daun Rhizophora apiculata Asal Perairan Teluk Awur, Jepara - Mirsa Septiana Mutik; Mada Triandala Sibero; Widianingsih Widianingsih; Subagiyo Subagiyo; Rudhi Pribadi; Dwi Haryanti; Ambariyanto Ambariyanto; Retno Murwani (Jurnal Kelautan Tropis, 2022)
Rhizophora apiculata is a type of mangrove that has the ability to adapt to extreme environmental conditions such as temperature, low oxygen levels, and high salinity. This adaptability affects the production of secondary metabolites. Information about the antibacterial activity of this mangrove against MDR (Multi-Drug Resistant) bacteria is still very limited. The content of secondary metabolites produced by mangrove R. apiculata is also expected to affect antioxidant activity against free radicals. The purposes of this study were to examine the presence of bioactive compounds by phytochemical tests and to evaluate the antibacterial activity against MDR bacteria such as Pseudomonas aeruginosa, Escherichia coli, Bacillus cereus, and Bacillus subtilis; and antioxidants property of R. Apiculata leaves that were collected from Teluk Awur, Jepara. The leaves were extracted using the multilevel maceration method with solvent sequence n-hexane, ethyl acetate and methanol. Metabolite finger printing using TLC method was carried out to detect the presence of alkaloids, flavonoids, saponins, phenolics, quinones, steroids, and triterpenoids. The antibacterial test was carried out using agar well diffusion method while the antioxidant test was carried out using the DPPH method. The results of the phytochemical test showed that there were groups of alkaloids and steroids in the n-hexane solvent; alkaloids, phenolics, and steroids in ethyl acetate solvent; as well as alkaloids, flavonoids, phenolics, and saponins in methanol solvents. The results of this study indicate that R. apiculata from Teluk Awur Coastal Waters, Jepara had no potential as an antibacterial against MDR (Multi-Drug Resistant) bacteria, however the methanol extract has the potential to be used as an antioxidant with an IC50 value of 85.999 ppm. The bioautography showed that compounds from the phenol group, flavonoids, triterpenoids and b-carotene pigments acted as antioxidant agents in the leaf extract of R. apiculata.